PENGARUH SELF EFFICACY TERHADAP MOTIVASI DAN KEPUASAN KERJA KARYAWAN INNA GRAND BALI BEACH HOTEL - Indra Parasara, Ida Bagus Agung; Surya, Ida Bagus Ketut (E-Jurnal Manajemen, 2016)
The purpose of this study was to determine the effect of Self - efficacy on motivation and job satisfaction of employees. The study was conducted on employees Inna Grand Bali Beach Hotel, Sanur with a number of respondents as many as 82 employees. The number of respondents is determined using proportional random sampling method, where respondents are employees other than top management. Data obtained by distributing questionnaires were analyzed using path analysis (path analysis). The test results get Self-efficacy and significant positive effect on employee job satisfaction, self-efficacy and significant positive effect on employee motivation, and motivation positive effect on employee satisfaction. To foster a sense of job satisfaction of employees, the management needs to motivate employees. In addition to improving the interaction between management and employees PIAK will also improve Self-eficacy inside employees who have an impact on job satisfaction felt by employees at work
Keywords: self-efficacy, motivation, job satisfaction